Axial bearing capacity of helical piles in moist and saturated conditions using frustum confining vessel (FCV) - Ali Jassim; Navid Ganjian; Abolfazl Eslami (Numerical Methods in Civil Engineering)
Due to the increasing demand in construction and use of different types of piles on the one hand and the high cost of conducting large-scale tests on different types of piles, on the other hand, new methods have been proposed to study the behavior of different types of piles. Physical modeling provides the researcher the capability of studying model piles in the scaled environment at low costs. Among the different methods of physical modeling, the use of frustum confining vessels (FCV) has gained attraction in recent years. FCV is a cone-shaped vessel that can produce a stress distribution similar to the idealized linear stress distribution in depth. Helical piles are common types of deep foundations which were first used about 200 years ago. Helical Apiles are driven to the soil by applying a torque to the end of piles in the presence of vertical loads. Their quick and noise-free installation method, the minimal disturbance during the installation, and  environmental compatibility make them popular for working in urban areas. In this research, using the finite element method, the optimal dimensions of FCV apparatus were selected, and the FCV apparatus with optimal dimensions were constructed. A total of 18 compression tests were performed on Anzali sand in different relative densities and moisture contents, using single-helix and three-helices piles. Results indicate that increasing the number of helices and relative density of soil increases the pile and sand contact and causes higher bearing capacity for helical piles. Soil saturation, on the other hand, significantly reduces the ultimate strength.